Genetic Codes of Housing: Morphological Reading of Traditional Antalya Houses - COŞKUN, ASLIHAN; Haştemoğlu, Hasan Şehmuz (MDPI, 2025)
This study focuses on the traditional houses of Kaleiçi, Haşim İşcan, and Balbey neighborhoods, which constitute the historical center of Antalya and reflect the cultural continuity of the organic urban texture dating back to the Hellenistic period. The aim is to reveal how climatic, topographic and cultural factors shape the spatial organization of these traditional houses. Using the space syntax method, the study analyzes nine sample houses to examine their morphological structure. The findings show that while the ground floors are mostly arranged as service areas and the upper floors as living spaces, the sofa emerges as the most integrated space despite varying depths across neighborhoods. Moreover, spatial differences between the neighborhoods indicate contextual diversity, yet the persistence of sofa-centered organization underlines the role of cultural continuity in housing morphology. By emphasizing the centrality of the sofa and demonstrating how cultural factors sustain typological patterns over time, this study contributes to the literature on space syntax-based morphology and offers practical insights for contemporary housing design that considers climatic and cultural contexts.
Keywords: Antalya; Historical Cities; Space Syntax; Spatial Analysis; Spatial Configuration; Traditional House